Self-compacting concrete prepared from concrete waste slurry and preparation method thereof

By mixing concrete waste slurry with activation composition to prepare regenerated admixtures and adding them to the concrete formula, the problems of concrete cracking and performance degradation caused by waste slurry are solved, and the effective utilization of waste slurry and the improvement of concrete performance are achieved.

CN119390411APending Publication Date: 2025-02-07WUHAN ZHONGYANGMING BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411508957.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The concrete prepared from waste slurry in concrete mixing stations has problems such as excessive drying and shrinking, causing cracking. Direct use of waste slurry water will affect the working performance, mechanical properties and durability of the concrete, resulting in the waste slurry not being fully utilized.

Method used

Regenerated admixtures are prepared by mixing concrete waste slurry with activation composition and added to the concrete formulation, using wet grinding operations and specific admixtures to improve the flow and mechanical properties of the concrete.

Benefits of technology

The effective utilization of concrete waste slurry is achieved. The self-solid concrete produced has good flow properties, does not segregate or exudate water, and the solidified concrete has high compressive strength and good crack resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005104878420000051
    Figure BDA0005104878420000051
  • Figure BDA0005104878420000071
    Figure BDA0005104878420000071
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete preparation, and discloses self-compacting concrete prepared from concrete waste slurry and a preparation method. The self-compacting concrete prepared from the waste concrete slurry is prepared from cement, fly ash, mineral powder, machine-made sand, stone, water, an additive and a regenerated admixture, the regenerated admixture is prepared from the waste concrete slurry and an activated composition, and the activated composition is prepared from ardealite, biomass hard carbon and water-based inorganic resin. The concrete waste slurry and the specific substance are mixed to prepare the regenerated admixture, the regenerated admixture is added into the concrete formula to prepare the self-compacting concrete, effective utilization of the concrete waste slurry is achieved, the prepared self-compacting concrete has the good flowing property and is free of segregation and bleeding, and the compressive strength of the cured concrete is high; the manufacturing process is simple and easy to operate, and is suitable for industrial popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete preparation, and in particular to a self-compacting concrete prepared by using concrete waste slurry and a preparation method thereof. Background Art

[0002] Concrete materials are still the most widely used building materials. They are mainly produced by concrete mixing plants, which inevitably produce a large amount of wastewater, waste slurry and waste residue. Concrete waste slurry contains a certain amount of cementitious material components, which are generally highly alkaline (pH value can reach above 13). Direct discharge into the surrounding natural environment is a great waste of cementitious materials and water resources. More importantly, it will bring huge environmental pollution, such as polluting clean groundwater sources, solid particles in wastewater silting up and blocking sewers, and forming new waste residues after hardening, which greatly affects the sustainable development of concrete mixing plant companies. A lot of work has been carried out around the preparation of concrete from concrete mixing plant waste slurry, and a series of beneficial results have been achieved. The recycling and reuse of concrete waste slurry has been studied and applied in some practical projects.

[0003] With the continuous deepening of relevant research, concrete prepared from waste slurry from concrete mixing plants also presents some obvious technical defects, such as excessive drying shrinkage that can easily cause concrete cracking. Directly using waste slurry water as mixing water to add to concrete will have adverse effects on the working performance, mechanical properties and durability of concrete. Therefore, most ready-mixed concrete companies currently only apply a small amount of waste slurry water to concrete and cannot fully utilize it. Therefore, it is necessary to combine the characteristics of concrete prepared from waste slurry from concrete mixing plants and develop a concrete that can better balance the flow properties and mechanical properties and realize the resource recycling of waste concrete slurry for application scenarios suitable for its large-scale use, so as to promote the green, environmental protection and sustainable development of the concrete production industry. Summary of the invention

[0004] In order to solve the above technical problems, a self-compacting concrete prepared using concrete waste slurry has been developed, which can utilize concrete waste slurry to a large extent, has good flowability, does not separate or bleed, and has good mechanical properties after solidification. The present application provides a self-compacting concrete prepared using concrete waste slurry and a preparation method.

[0005] In a first aspect, the present application provides a self-compacting concrete prepared using waste concrete slurry, comprising the following components in parts by weight: 350 parts of cement, 50-80 parts of fly ash, 130-150 parts of mineral powder, 650-900 parts of machine-made sand, 800-1000 parts of gravel, 120-150 parts of water, 40-50 parts of admixture, and 120-180 parts of recycled admixture; the recycled admixture is prepared from concrete waste slurry and an activated composition in a weight ratio of 1:0.3-0.5, and the raw materials of the activated composition include phosphogypsum, biomass hard carbon and water-based inorganic resin in a weight ratio of (2-4): (0.2-0.3): (0.4-0.6).

[0006] By adopting the above technical scheme, the present application adopts the activated composition and concrete waste slurry as admixtures to prepare self-compacting concrete, uses water-based inorganic resin and biomass hard carbon to activate phosphogypsum, rationally utilizes concrete waste slurry and phosphogypsum, reduces the pollution of concrete waste slurry and phosphogypsum to the environment and saves resources, generates highly active metastable substances by solid phase reaction at high temperature, improves the activity of materials, uses wet grinding operation, and while the particles become smaller, the contact between biomass hard carbon and phosphogypsum becomes closer, thereby further improving the activity of the mixture, and the biomass hard carbon and phosphogypsum that lose free water can reduce the slump loss of concrete, thereby improving the workability and compressive strength of the self-compacting concrete obtained. After mixing the concrete waste slurry and the activated composition, a small amount of calcium sulfonate is generated under the stimulation of phosphogypsum, which is small in size and has the effect of crystal nucleus induction in the early stage of cement hydration, promoting the formation of nano calcium sulfonate, which not only has a good thickening effect, but also has an enhanced effect. The recycled admixture in the present application can also coat the machine-made sand, which can effectively fill the pores of the machine-made sand, making the surface of the sulfur machine-made sand smoother and the shape more regular, thereby promoting the dispersion of the machine-made sand in the cement mortar, which is beneficial to reduce the generation of large pores in the mortar, and can greatly reduce the loss rate of free water in the pores of the mortar, thereby improving the anti-cracking performance of the self-compacting concrete obtained.

[0007] Optionally, the slurry generation time of the waste concrete slurry is within 30 hours, the waste concrete slurry is the waste concrete slurry after filtration treatment, and the density of the waste concrete slurry after filtration treatment is controlled at 1.02-1.04 g / cm3.

[0008] Optionally, the method for preparing the activation composition comprises the following steps: T1. Wash, dry and crush the biomass raw material to obtain biomass powder, pre-calcine a mixture of biomass powder and ferric chloride in a weight ratio of 100:1 under a protective gas atmosphere, impregnate the pre-calcined product into epoxy resin, take it out, and carbonize it under a protective gas atmosphere to obtain biomass hard carbon for standby use; T2. Crush the phosphogypsum, dry it at 120-150°C for 2-5h, add the aqueous inorganic resin and the biomass hard carbon obtained in step T2, wet grind it to a solid content of 40-50wt%, dry it at 100-120°C, calcine it at 500-600°C for 2-3h, dry grind it, sieve it, and obtain an activated composition.

[0009] Optionally, in step T1, the biomass raw material is washed, dried, and crushed to 200 mesh to obtain biomass powder, and a mixture of biomass powder and ferric chloride in a weight ratio of 100:1 is pre-calcined at 300°C for 2 hours under an argon atmosphere, and the pre-calcined product is impregnated into bisphenol A epoxy resin with an impregnation amount controlled to 10wt%, taken out, and carbonized at 1400°C for 2 hours under an argon atmosphere to obtain biomass hard carbon for later use.

[0010] By adopting the above technical solution, the biomass hard carbon material itself has a large number of internal lattice defects, produces a large number of active sites, and has a huge specific surface area. After being activated together with phosphogypsum, it has strong water absorption and can play the role of a "water reservoir". It can effectively improve the internal structure of concrete and enhance the ability of concrete to resist drying shrinkage.

[0011] Optionally, the biomass raw material is selected from one of lychee wood, apple wood, poplar wood, bamboo, fruit shell, straw, coconut shell and corn cob.

[0012] Optionally, the method for preparing the recycled admixture comprises the following steps: mixing concrete waste slurry with an activation composition, stirring at 70-90° C. for 3-5 hours, and standing for 5-8 hours to obtain the recycled admixture.

[0013] Optionally, the admixture includes polyethylene glycol, polycarboxylic acid water reducer, sodium tripolyphosphate and urea in a weight ratio of 20-30:10-15:3-6:5-8.

[0014] By adopting the above technical scheme, polyethylene glycol can improve the fluidity and plasticity of concrete; polycarboxylate water reducer can significantly reduce the water consumption of concrete and the amount of cementitious materials used; sodium tripolyphosphate as a dispersant can improve the dispersibility of cement particles, reduce flocculation inside cement, and improve the workability of concrete; urea plays the role of a retarder to prevent the concrete from coagulating too quickly; polyethylene glycol, polycarboxylate water reducer, sodium tripolyphosphate and urea are compounded as admixtures to give full play to the "interface effect" and "water reduction effect", improve rheological properties, reduce hydration heat, and reduce segregation and bleeding.

[0015] Optionally, the fineness modulus of the machine-made sand is 2.3-3.0, and the mass content of stone powder is about 12%.

[0016] Optionally, the stones include large stones and small stones, the particle size of the large stones is 8-28 mm, the particle size of the small stones is 3.5-7.9 mm, and the weight ratio of the large stones to the small stones is 5-6:2-4.

[0017] Optionally, the fly ash is Grade II fly ash, with a water requirement ratio of 95-98% and a loss on ignition of ≤4.5%; the mineral powder is Grade S95 mineral powder, with a specific surface area of ​​400-450m 2 / kg, the activity index after 28 days was 95%, and the fluidity ratio was 99%.

[0018] Optionally, the aqueous inorganic resin is potassium silicate, and the solid content is 40.0±0.2wt%.

[0019] In a second aspect, the present application provides a method for preparing the self-compacting concrete using the above-mentioned waste concrete slurry, comprising the following steps: S1. Mix cement, fly ash, machine-made sand, gravel and mineral powder to prepare a premix; S2. After mixing the admixture with water, add the recycled admixture and stir, add the premix and mix, so as to obtain a self-compacting concrete prepared by using the concrete waste slurry.

[0020] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The present application achieves effective utilization of concrete waste slurry by mixing concrete waste slurry with specific substances to form a recycled admixture, and adding the recycled admixture into a concrete formula to prepare self-compacting concrete. The self-compacting concrete prepared in the present application has good flowability, no segregation, and no water seepage. The cured concrete has high compressive strength and good crack resistance.

[0021] 2. The raw materials used in this application are from a wide range of sources, and various industrial wastes are also used, which has important practical significance for green development; the production process is simple and easy to operate, and is suitable for industrial promotion and use. DETAILED DESCRIPTION

[0022] The present application designs a self-compacting concrete prepared using concrete waste slurry, comprising the following components in parts by weight: 350 parts of cement, 50-80 parts of fly ash, 130-150 parts of mineral powder, 650-900 parts of machine-made sand, 800-1000 parts of gravel, 120-150 parts of water, 40-50 parts of admixture, and 120-180 parts of recycled admixture; the recycled admixture is prepared from concrete waste slurry and an activation composition in a weight ratio of 1:0.3-0.5, and the raw materials of the activation composition include phosphogypsum, biomass hard carbon and water-based inorganic resin in a weight ratio of (2-4): (0.2-0.3): (0.4-0.6).

[0023] The self-compacting concrete prepared by using waste concrete slurry in the present application is prepared by the following method, including the following steps: S1. Mix cement, fly ash, machine-made sand, gravel and mineral powder to prepare a premix; S2. After mixing the admixture with water, add the recycled admixture and stir, add the premix and mix, so as to obtain a self-compacting concrete prepared by using the concrete waste slurry.

[0024] The technical problem solved by this application is that concrete prepared from waste slurry from concrete mixing plants also presents some obvious technical defects, such as excessive drying shrinkage that can easily cause concrete cracking. Directly using waste slurry water as mixing water to mix into concrete will have adverse effects on the working performance, mechanical properties and durability of concrete, so concrete waste slurry cannot be fully utilized. This application achieves effective utilization of concrete waste slurry by mixing concrete waste slurry with specific substances to make recycled admixtures, adding them to concrete formulas to make self-compacting concrete. The self-compacting concrete prepared by this application has good flow properties, no segregation, no water seepage, and the solidified concrete has high compressive strength and good crack resistance.

[0025] The present application is further described in detail below with reference to the embodiments.

[0026] Preparation Example 1-3 Preparation Examples 1-3 are regeneration admixtures made from different raw materials, the difference being that the raw material ratios in the activation composition are different.

[0027] The recycled admixture in Preparation Example 1 includes concrete waste slurry and an activation composition in a weight ratio of 1:0.4; wherein the activation composition includes phosphogypsum, biomass hard carbon and water-based inorganic resin in a weight ratio of 3:0.25:0.5.

[0028] The recycled admixture in Preparation Example 2 includes concrete waste slurry and an activation composition in a weight ratio of 1:0.4; wherein the activation composition includes phosphogypsum, biomass hard carbon and water-based inorganic resin in a weight ratio of 2:0.2:0.6.

[0029] The recycled admixture in Preparation Example 3 includes concrete waste slurry and an activation composition in a weight ratio of 1:0.4; wherein the activation composition includes phosphogypsum, biomass hard carbon and water-based inorganic resin in a weight ratio of 4:0.3:0.4.

[0030] The waste concrete slurry used in Preparation Examples 1-3 is from the same batch of waste concrete slurry. The slurry of the waste concrete slurry was produced within 24 hours. After filtering to remove insoluble impurities, the density of the waste concrete slurry was controlled to be 1.04 g / cm 3The waste concrete slurry was analyzed for water quality and found to be in compliance with the water requirements for reinforced concrete in JGJ63-2006 "Concrete Water Standard". The measured data were as follows: pH value 10.8; insoluble matter content 15490; soluble matter content 2850; chloride content 194; sulfate content 269; and alkali content 1485.

[0031] The preparation method of the activation composition used in Preparation Examples 1-3 comprises the following steps: T1, wash the bamboo, dry it at 50°C, and crush it to 200 mesh to obtain biomass powder, pre-calcine a mixture of biomass powder and ferric chloride in a weight ratio of 100:1 at 300°C for 2h under an argon atmosphere, impregnate the pre-calcined product into bisphenol A epoxy resin, and control the impregnation amount to 10wt%, take it out, and carbonize it at 1400°C for 2h under an argon atmosphere to obtain biomass hard carbon for standby use; T2. Grind the phosphogypsum into 200 mesh, dry it at 120°C for 2.5 hours, add the aqueous inorganic resin and the biomass hard carbon obtained in step T1, add water and wet grind to a solid content of 50wt%, dry it at 120°C, calcine it at 600°C for 3 hours, dry grind it, sieve it, and obtain an activated composition.

[0032] The calcium sulfate dihydrate (dry basis) content of the phosphogypsum used in Preparation Examples 1-3 is up to 92wt%, the water-soluble phosphorus pentoxide (dry basis) content is 0.03wt%, the water-soluble fluoride ion (dry basis) content is less than 0.01wt%, the water-soluble magnesium oxide (dry basis) content is 0.06wt%, and the chloride ion (dry basis) content is less than 0.01wt%.

[0033] The main component of the aqueous inorganic resin used in Preparation Example 1-3 is potassium silicate, and the solid content is 40 wt%.

[0034] Preparation Example 4-5 Preparation Example 4 is based on Preparation Example 1, except that the recycled admixture in Preparation Example 4 includes concrete waste slurry and an activation composition in a weight ratio of 1:0.3.

[0035] Preparation Example 5 is based on Preparation Example 1, except that the recycled admixture in Preparation Example 5 includes concrete waste slurry and an activation composition in a weight ratio of 1:0.5.

[0036] Examples 1-5 Examples 1-5 are self-compacting concretes made from different raw materials, the difference being that the raw material ratios are different. The specific raw material ratios are shown in Table 1 (unit: parts by weight).

[0037] Table 1 The fineness modulus of the machine-made sand used in Examples 1-5 is between 2.3 and 3.0, corresponding to medium sand, with a particle size distribution in the range of 1.18-2.36 mm, and a stone powder mass content of about 12%.

[0038] The cement used in Examples 1-5 is Portland cement.

[0039] The fly ash used in Examples 1-5 is Class II fly ash, with a water requirement ratio of 95% and a loss on ignition of ≤4.5%.

[0040] The weight ratio of large stones to small stones in the stones used in Examples 1-5 is 6:4, wherein the average particle size of the large stones is 22 mm, and the average particle size of the small stones is 6 mm.

[0041] The mineral powder used in Examples 1-5 is S95 grade mineral powder with a specific surface area of ​​400-450m 2 / kg, the activity index after 28 days was 95%, and the fluidity ratio was 99%.

[0042] The admixture used in Examples 1-5 includes a mixture of polyethylene glycol, polycarboxylate water reducer, sodium tripolyphosphate and urea in a weight ratio of 25:11:5:6; wherein the polycarboxylate water reducer is purchased from SR-7302 concrete water reducer of Lianhong New Materials Technology.

[0043] The regenerated admixture used in Examples 1-5 is the regenerated admixture prepared in Preparation Example 1.

[0044] The method for preparing the self-compacting concrete in Examples 1-5 comprises the following steps: S1. Mix cement, fly ash, machine-made sand, gravel and mineral powder, stir evenly to prepare a premix; S2. After mixing the admixture with water, add the recycled admixture and stir evenly, add the premix and mix evenly to obtain a self-compacting concrete prepared using concrete waste slurry.

[0045] Embodiment 6-9 Examples 6-9 are self-compacting concretes made from different raw materials. The difference lies in the different recycled admixtures used. See Table 2 for details.

[0046] Table 2 Self-compacting concrete Recycled admixture Example 6 Preparation Example 2 Example 7 Preparation Example 3 Example 8 Preparation Example 4 Example 9 Preparation Example 5 Comparative Example 1 Comparative Example 1 is based on Example 2, with the difference that when preparing the regenerated admixture in Comparative Example 1, the biomass hard carbon is replaced by graphite.

[0047] Comparative Example 2 Comparative Example 2 is based on Example 2, with the difference that when preparing the regenerated admixture in Comparative Example 2, phosphogypsum is replaced by limestone.

[0048] Performance Testing Self-compacting concrete was prepared according to Examples 1-9 and Comparative Examples 1-2, and various properties of the concrete were tested according to the following methods. The test results are recorded in Table 3: 1. With reference to the standard GB / T50081-2002 "Test methods for mechanical properties of ordinary concrete", the compressive strength of the self-compacting concrete prepared in Examples 1-9 and Comparative Examples 1-2 after curing at 3d, 7d and 28d, respectively.

[0049] 2. The expansion of the self-compacting concrete prepared in Examples 1-9 and Comparative Examples 1-2 was tested with reference to the standard GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures".

[0050] Table 3 By analyzing the data in Table 3, the self-compacting concrete prepared in the present application has a high initial expansion degree. The self-compacting concrete prepared in Examples 1-9 has good working performance of the mixture during the experiment, and no segregation and bleeding occurs. However, the self-compacting concrete in Comparative Examples 1 and 2 has good flowability but poor mechanical properties, and obvious segregation and bleeding occur during the working process of the mixture.

[0051] In summary, the self-compacting concrete prepared in the present application has good flow properties, no segregation, no water seepage, and the concrete has high compressive strength after curing.

[0052] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A self-compacting concrete prepared using waste concrete slurry, characterized in that: The composition comprises the following components in parts by weight: 350 parts of cement, 50-80 parts of fly ash, 130-150 parts of mineral powder, 650-900 parts of machine-made sand, 800-1000 parts of gravel, 120-150 parts of water, 40-50 parts of admixture, 120-180 parts of recycled admixture; The regenerated admixture is prepared from concrete waste slurry and an activation composition in a weight ratio of 1:0.3-0.5, and the raw materials of the activation composition include phosphogypsum, biomass hard carbon and water-based inorganic resin in a weight ratio of (2-4): (0.2-0.3): (0.4-0.6).

2. The self-compacting concrete prepared by using waste concrete slurry according to claim 1, characterized in that: The slurry of the waste concrete slurry is generated within 30 hours, and the waste concrete slurry is the waste concrete slurry after filtration treatment, and the density of the waste concrete slurry after filtration treatment is controlled at 1.02-1.04 g / cm 3 .

3. The self-compacting concrete prepared by using waste concrete slurry according to claim 1, characterized in that: The preparation method of the activation composition comprises the following steps: T1. Wash, dry and crush the biomass raw material to obtain biomass powder, pre-calcine a mixture of biomass powder and ferric chloride in a weight ratio of 100:1 under a protective gas atmosphere, impregnate the pre-calcined product into epoxy resin, take it out, and carbonize it under a protective gas atmosphere to obtain biomass hard carbon for standby use; T2. Crush the phosphogypsum, dry it at 120-150°C for 2-5h, add the aqueous inorganic resin and the biomass hard carbon obtained in step T2, wet grind it to a solid content of 40-50wt%, dry it at 100-120°C, calcine it at 500-600°C for 2-3h, dry grind it, and sieve it to obtain an activated composition.

4. The self-compacting concrete prepared by using waste concrete slurry according to claim 3, characterized in that: The biomass raw material is selected from one of lychee wood, apple wood, poplar wood, bamboo, fruit shell, straw, coconut shell and corn cob.

5. The self-compacting concrete prepared by using waste concrete slurry according to claim 1, characterized in that: The preparation method of the regenerated admixture comprises the following steps: mixing concrete waste slurry with an activation composition, stirring at 70-90° C. for 3-5 hours, and standing for 5-8 hours to obtain the regenerated admixture.

6. The self-compacting concrete prepared by using waste concrete slurry according to claim 1, characterized in that: The admixture comprises polyethylene glycol, polycarboxylic acid water reducer, sodium tripolyphosphate and urea in a weight ratio of 20-30:10-15:3-6:5-8.

7. The self-compacting concrete prepared by using waste concrete slurry according to claim 1, characterized in that: The fineness modulus of the machine-made sand is 2.3-3.0, and the mass content of stone powder is about 12%.

8. The self-compacting concrete prepared by using waste concrete slurry according to claim 1, characterized in that: The aqueous inorganic resin is potassium silicate, and the solid content is 40.0±0.2wt%.

9. A method for preparing self-compacting concrete using waste concrete slurry according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Mix cement, fly ash, machine-made sand, gravel and mineral powder to prepare a premix; S2. After mixing the admixture with water, add the recycled admixture and stir, add the premix and mix, so as to obtain a self-compacting concrete prepared by using the concrete waste slurry.